Salmon-Igm Functionalized-Plga Nanosystem for Florfenicol Delivery as an Antimicrobial Strategy Against Piscirickettsia Salmonis - Reyes-Lopez, F; Vallejos-Vidal, E (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Salmonid rickettsial septicemia (SRS), caused by Piscirickettsia salmonis, has been the most severe health concern for the Chilean salmon industry. The efforts to control P. salmonis infections have focused on using antibiotics and vaccines. However, infected salmonids exhibit limited responses to the treatments. Here, we developed a poly (D, L-lactide-glycolic acid) (PLGA)-nanosystem functionalized with Atlantic salmon IgM (PLGA-IgM) to specifically deliver florfenicol into infected cells. Polymeric nanoparticles (NPs) were prepared via the double emulsion solvent-evaporation method in the presence of florfenicol. Later, the PLGA-NPs were functionalized with Atlantic salmon IgM through carbodiimide chemistry. The nanosystem showed an average size of ~380–410 nm and a negative surface charge. Further, florfenicol encapsulation efficiency was close to 10%. We evaluated the internalization of the nanosystem and its impact on bacterial load in SHK-1 cells by using confocal microscopy and qPCR. The results suggest that stimulation with the nanosystem elicits a decrease in the bacterial load of P. salmonis when it infects Atlantic salmon macrophages. Overall, the IgM-functionalized PLGA-based nanosystem represents an alternative to the administration of antibiotics in salmon farming, complementing the delivery of antibiotics with the stimulation of the immune response of infected macrophages. © 2024 by the authors.